Apego: evolução da relação e discriminação do objeto - Almeida, Leila Sanches de (1988)
This study investigates some results of a recent 1nvestigation by Almeida, Colinvaux, Pardal and Penna (1985). One general hypothesis was tested: in day-care center children, the development of the object permanence concept is related to the development of attachment to the caretaker. The theoretical models for this study are J. Piaget's cognitive development theory (specially his explanation of the development of the notion of inanimate objects as permanent entities) and J. Bowlby's attachment theory. A sample of 39 children, aged from 0,6 to 2;0 and who spent all day in day-care centers was studied. The children were administered the series 'search of the missing object' from Casati and Lezine's scale (1968) and were also observed in a laboratory situation derived from Ainsworth and Wittig' s strange situation (1969). No significative relation was found between the two variables studied, although data shows a trend in this direction. The author suggests future investigations larger samples. She also proposes that the concept of using person permanence could be another variable to be considered in future investigations.